Usage Characteristics of Mobile Telecommunication Services: Individual Service Recipient Perspective in Rajshahi District of Bangladesh - Hossain, Md. Zahid (Global Disclosure of Economics and Business, 2022)
Mobile telecommunication services proved to be a significant part of everyday life for the people of Bangladesh. The study’s primary purpose was to examine the usage characteristics of subscribers to know the reality through an empirical study. The research study was descriptive and quantitative in approach to drawing meaningful facts. This study was conducted in the Rajshahi district in the northern region of Bangladesh. The sample size resulted in three hundred and seventy-eight for completing the survey. A simple random sampling technique was used to draw samples from male and female sampling units. The research used a cross-sectional survey design to collect primary data. In addition, the researcher administered a structured questionnaire as a research tool to find out the facts from the individual service recipients. Research findings show that individual service recipients’ usage characteristics influence the service marketing mix and brand equity to achieve a competitive advantage. For example, the study found that consumers are more interested in using services other than voice calls through their affordability does not support it. Moreover, responses from service recipients varied significantly, which becomes a significant challenge for the operators to blend the elements of the marketing mix. This study also shed light on the Inconvenience or problems the recipients face in consuming services. For example, the topmost inconvenience service recipients face is ’poor service quality’ like network interruption, poor quality network, and poor quality video streaming experience. Finally, the study suggests mobile operators in Bangladesh need to trigger a marketing mix by consistently considering the dynamism of usage characteristics of individual service recipients to utilize their marketing investment, increase brand equity, and achieve a significant competitive advantage.